Influence of chemical bonding of chlorides with aluminates in cement hidratation process on corrosion steel bars in concrete - Bikic, Farzet (Hemijska industrija, 2010)
The presence of chlorides in concrete is a permanent subject of research because they cause corrosion of steel bars. Chlorides added to the concrete during preparation, as accelerators of the bonding of cement minerals process, enter into reaction with aluminates, creating a phase known as chloroaluminate hydrates. In everyday conditions the product of chemical bonding between chlorides and aluminates is usually monochloridealuminate C3A?CaCl2?Hx, better known as Friedel's salt. In this paper, the influence of chemical bonding of chlorides with aluminates during the process of cement hydration on corrosion of steel bars in concrete was investigated. The process of chlorides bonding with aluminates yielding monochloride aluminate is monitored by XRD analyses. It was found that the amount of chlorides bonding with aluminates increases with an increase of temperature, and as a result, reduces the amount of 'free' chlorides in concrete. Potentiodynamic measurements have shown that increase in temperature of the heat treatment of working electrodes by chlorides leads to a reduction of steel bars corrosion as a result of either the increase of the monochloride-aluminate content or the decrease of free chlorides amount. Chlorides bound in chloroaluminate hydrates do not cause activation of steel bars corrosion in concrete. It was also proven that the increase of free chlorides concentration in the concrete leads to intensification of steel bars corrosion. This additionally approves that free chlorides are only the activators of process of steel bars corrosion in the concrete. Hloridi prisutni u betonu stalni su predmet istrazivanja zbog uzrokovanja korozije celicne armature. Hloridi dodavani u beton prilikom pripreme, u svojstvu ubrzivaca procesa vezivanja cementnih minerala, stupaju u reakcije s aluminatima, gradeci faze znane kao hloraluminat hidrati. U ovom radu je istrazivan uticaj hemijskog vezivanja hlorida za aluminate u procesu hidratacije cementa na koroziju celicne armature u betonu. Rezultati ovog rada pokazuju kako se povecanjem intenziteta vezivanja hlorida za aluminate smanjuje intenzitet korozije na celicnoj armaturi u betonu. Takodje je dokazano da porast koncentracije slobodnih hlorida u betonu dovodi do porasta intenziteta korozije celicne armature.